Mediação da informação através de plataformas digitais: práticas nas bibliotecas, arquivos e museus da área metropolitana do Porto - Dayane dos Santos Farias (2018)
The main goal of this study was to investigate how mediation occurs through digital platforms managed by libraries, archives and museums within the metropolitan area of Porto. This study was conducted in 17 municipalities of the metropolitan area of Porto. Thus, this was an exploratory and descriptive research with a qualitative and quantitative approach. For data collection, we used the participant observation methodology and applied a structured survey to analyze and characterize the digital platforms with respect to information updating and user interaction. In addition to the literature review and data collection, we analyzed social platforms, Facebook and blogs, as well as websites of the services using an adapted version of the model employed by Amaral e Guimarães (2002) and Guia de Boas Práticas na Construção de Web Sites da Administração Directa e Indirecta do Estado (2003), which contains criteria for evaluating websites. Our findings suggest that further expansion and improvements of the library and archive services with regard to digital technologies need to be revised and the involvement of trained professionals to be responsible for the mediation through digital platforms is required. Therefore, the integration between digital environment and human resources is now necessary for improving the mediation of the information within these services. Keywords: Information mediation; Digital platforms; Metropolitan Area of Porto; Library; Archive; Museum